Phenoxide and alkoxide complexes of Mg, Al and Zn, and their use for the ring‐opening polymerization of ϵ‐caprolactone with initiators of different natures. Issue 5 (14th April 2018) - Minyaev, Mikhail E.; Nifant'ev, Ilya E.; Shlyakhtin, Andrey V.; Ivchenko, Pavel V.; Lyssenko, Konstantin A.
Abstract : The structures of a new packing polymorph of Mg(O‐2, 6‐ t Bu2 ‐4‐MeC6 H4 )2 (THF)2 and of a dimeric complex [Al(CH3 )(O‐2, 6‐ t Bu2 ‐4‐MeC6 H4 )(μ2 ‐OCH2 COOC2 H5 )]2 have been determined. The structure of [Zn7 (C2 H5 )6 (μ3 ‐OCH2 Ph)8 ], possessing a bicubic Zn7 O8 core, has been redetermined. The complexes have been tested as catalysts (Al and Zn) and as a precatalyst (Mg) for the ring‐opening polymerization of ϵ‐caprolactone. Abstract : A new packing polymorph of bis(2, 6‐di‐ tert ‐butyl‐4‐methylphenolato‐κ O )bis(tetrahydrofuran‐κ O )magnesium, [Mg(C15 H23 O)2 (C4 H8 O)2 ] or Mg(BHT)2 (THF)2, (BHT is the 2, 6‐di‐ tert ‐butyl‐4‐methylphenoxide anion and THF is tetrahydrofuran), (1 ), has the same space group ( P 21 ) as the previously reported modification [Nifant'ev et al. (2017 d ). Dalton Trans. 46, 12132–12146], but contains three crystallographically independent molecules instead of one. The structure of (1 ) exhibits rotational disorder of the tert ‐butyl groups and positional disorder of a THF ligand. The complex of bis(2, 6‐di‐ tert ‐butyl‐4‐methylphenolato‐κ O )bis(μ2 ‐ethyl glycolato‐κ 2 O, O ′:κ O )dimethyldialuminium, [Al2 (CH3 )2 (C4 H7 O3 )2 (C15 H23 O)2 ] or [(BHT)AlMe(OCH2 COOEt)]2, (2 ), is a dimer located on an inversion centre and has an Al2 O2 rhomboid core. The 2‐ethoxy‐2‐oxoethanolate ligand (OCH2 COOEt) displays a μ2 ‐κ 2 O, O ′:κ O semi‐bridging coordination mode, forming a five‐membered heteronuclear Al–O–C–C–O ring. The same ligand exhibits positional disorder of the terminal methyl group. The redetermined structure of the heptanuclear complex octakis(μ3 ‐benzyloxo‐κ O :κ O :κ O )hexaethylheptazinc, [Zn7 (C2 H5 )6 (C7 H7 O)8 ] or [Zn7 (OCH2 Ph)8 Et6 ], (3 ), possesses a bicubic Zn7 O8 core located at an inversion centre and demonstrates positional disorder of one crystallographically independent phenyl group. Cambridge Structural Database surveys are given for complexes structurally analogous to (2 ) and (3 ). Complexes (2 ) and (3 ), as well as derivatives of (1 ), are of interest as catalysts for the ring‐opening polymerization of ϵ‐caprolactone, and polymerization results are reported.